2016
DOI: 10.1111/eos.12301
|View full text |Cite
|
Sign up to set email alerts
|

Influences of bicarbonate on processes of enamel subsurface remineralization and demineralization: assessment using micro-Raman spectroscopy and transverse microradiography

Abstract: In the present study, we investigated, using micro-Raman spectroscopy (Raman) and transverse microradiography, the influence of bicarbonate [sodium hydrogen carbonate (NaHCO )] on the effects of carbonate ions in the mineral phase during demineralization (acid resistance test) of subsurface lesions. Baseline lesions were created by demineralizing bovine enamel, and specimens were then exposed to remineralization solutions containing 0, 5, or 50 mM bicarbonate. Acid resistance tests were performed on reminerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The non-invasive nature of this technique enables correlating the mineral contents to the mechanical properties of the surface by using the same areas. Although the mineral distribution was previously investigated, [ 21 ] no previous study was conducted to assess the structural alteration in enamel following various surface treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The non-invasive nature of this technique enables correlating the mineral contents to the mechanical properties of the surface by using the same areas. Although the mineral distribution was previously investigated, [ 21 ] no previous study was conducted to assess the structural alteration in enamel following various surface treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial saliva is a remineralizing solution containing calcium ions and phosphate ions, which has been used in several experiments 18,21,[25][26][27] . In this study, a solution containing casein was used.…”
Section: Discussionmentioning
confidence: 99%
“…The coated specimens were immersed in AS (1.5 mM CaCl 2, 0.9 mM KH2PO4, 130 mM KCl, 20 mM Hepes, Casein 100 µg/mL, 0.02% NaN3, pH 6.8, 37°C) 18,21,[25][26][27] or DW for 14 days with their solution changed after 7 days. Sixty milliliters of solution was added to each container housing six samples.…”
Section: Artificial Saliva or Deionized Water Immersionmentioning
confidence: 99%
“…18 Investigators in several studies have evaluated whether sodium bicarbonate interferes with the remineralization of enamel subsurface carious lesions and their subsequent acid resistance. 19,20 Tanaka and Iijima 19 showed that the combination of fluoride and bicarbonate increased acid resistance more than each of them did alone. Kuramochi and colleagues 20 found that in the presence of bicarbonate, carbonate ions were incorporated into enamel lesions during remineralization; however, the extent of remineralization or acid resistance was not affected.…”
Section: Effect Of Baking Soda On Enamel Remineralizationmentioning
confidence: 99%